Cold War 2.0 : artificial intelligence in the new battle between China, Russia and America - Takach, George S. (New York: Pegasus Books, 2024)
"So much of what we hear about China and Russia today likens the relationship between these two autocracies and the West to a "rivalry" or a "great-power competition." Some might consider it alarmist to say we are in the midst of a second Cold War, but that may be the only responsible way to describe today's state of affairs. What's more, we have come a long way from Mao Zedong's infamous observation that "political power grows out of the barrel of a gun." Now we live in an age more aptly described by Vladimir Putin's cryptic prophecy that "artificial intelligence is the future not only of Russia, but of all mankind, and whoever becomes the leader in this sphere will become ruler of the world."
Technology and national power -- Cold War 1: autocracy, democracy, and technology -- The emergence of China -- Storm clouds and near wars -- The contest for artificial intelligence supremacy -- The contest for semiconductor chip supremacy -- The contest for quantum computing supremacy -- The contest for biotechnology Supremacy -- Other important technologies -- Other powerful assets -- Cold War 2.0 flashpoints -- Managing Cold War 2.0 -- Strengthening democracies -- A world technologically decoupled -- Coda.
Keywords: Artificial Intelligence -- Political Aspects; Intelligence Artificially -- Aspect politique; United States -- Foreign Relations -- China; United States -- Foreign Relations -- Russia (Federation)